Anticonvulsant Activity of Hydroalcoholic Extract of Ageratum Conyzoides L. (Asteraceae) in Mice - Randrianavony, Patricia; Quansah, Nat; Djoudi, Roukia; Quansah, Nyamekye A.; Randimbivololona, Fanantenanirainy (European Scientific Journal, ESJ, 2020)
This work aimsto study the anticonvulsant activity in vivo of the hydro alcoholic extract of Ageratum conyzoides L. (ASTERACEAE) in mice. Seizure was induced by electric stimulation of animal ears and intraperitoneal injection of picrotoxin. The extract increases the seizure threshold and reduces picrotoxin-induced convulsion duration. Animals of control group reacted to electric shock of 10.67 ± 0.74 mV, versus 14.33 ± 0.64, 22.67 ± 1.28 and 29.33 ± 0.64 mV for the animals treated with the extract at doses 200, 400 and 800 mg/kg respectively (P<0.05). Duration of clonic seizure induced by picrotoxin decreases from 36.04 ± 3.46 s in control group to 31.33 ± 0.88, 14.08 ± 1.02 and 10.07 ±1.31 s in the treated animals, while tonic seizure duration in control group is equal to 156.33 ± 24.53 s versus 73.02 ± 5.32 s and 29.67 ± 3.59 s in the animals treated with the extract at doses 400 and 800 mg/kg respectively (P<0.05). Alkaloids in the extract might be responsible for this activity by blocking Na+ or K+ channels, it also might enhance GABA or inhibit glutamate action.